KADAR ALBUMIN IKAN BETOK (Anabas testudineus) PADA SUNGAI DESA CENNING KECAMATAN MALANGKE LUWU UTARA - Nurmalasari; Rafika Wulandari; Ridha Yulyani Wardi (Cokroaminoto Journal of Chemical Science, 2020)
Betok fish (Anabas Testudineus) is a fish with high protein but there is no information about the albumin content in betok fish. This study aims to determine the albumin of Betok Fish (Anabas Testudineus) in Cenning, West Malangke District, North Luwu Regency. The measurement of albumin used the Lowry method with samples of adult fish of different sizes. The albumin content increases with increasing length and width of fish.